Potential and perspectives for establishing protected areas in El-Jabal El-Akhdar region, northeast Libya; an overview and example from ‘El-Abyar area’ - Manam W. B. Saaed; Aqeelah B. Ali; Yacoub M. El-Barasi; Rebeh O. Rahil (Brawijaya University, 2022)
This study was conducted in El-Abyar area in El-Jabal El-Akhdar region, northeast Libya. The aim was to study the environmental settings and the potential and possibility of establishing a protected area in this important region from a historical, biological, social, and economic point of view. The methodology included an intensive literature review, distribution of 300 questionnaires, soil and water analysis, fauna and flora survey, in addition to extensive field observation during the period from 2011 to 2021. The study highlighted the significant representative state of the study area for the whole El-Jabal El-Akhdar region in terms of environmental conditions and inappropriate anthropogenic pressure. Although the area has been severely degraded due to the arid climate coupled with decades of mismanagement, it still has remarkable ecological and environmental features and there is a feasible possibility of being converted into an effective protected area for biodiversity conservation with sustainable use of its natural resources by the local population (Category VI on the International Union for Conservation of Nature Classification for protected areas). The remaining barriers for which drastic solutions need to be implemented are a lack of awareness, a lack of protected areas guidelines and national perspectives, interest conflict with local people, a lack of constant funding, and failure of legislation enforcement.